Upper limit of the electrocaloric peak in lead-free ferroelectric relaxor ceramics - Le,Goupil F; Alford,NM (APL Materials, 2016)
The electrocaloric effect (ECE) of two compositions (x = 0.06 and 0.07) of (1 − x)(Na0.5Bi0.5)TiO3-xKNbO3 in the vicinity of the morphotropic phase boundary is studied by direct measurements. ΔTmax = 1.5 K is measured at 125 °C under 70 kV/cm for NBT-6KN while ΔTmax = 0.8 K is measured at 75 °C under 55 kV/cm for NBT-7KN. We show that the “shoulder,” TS, in the dielectric permittivity, marks the upper limit of the ECE peak under high applied electric fields. These results imply that the range of temperature with high ECE can be quickly identified for a given composition, which will significantly speed up the process of materials selection for ECE cooling.